2015
DOI: 10.1038/srep14226
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the inhibition of voltage-dependent K+ channel by gating modifier toxin

Abstract: Voltage-dependent K+ (Kv) channels play crucial roles in nerve and muscle action potentials. Voltage-sensing domains (VSDs) of Kv channels sense changes in the transmembrane potential, regulating the K+-permeability across the membrane. Gating modifier toxins, which have been used for the functional analyses of Kv channels, inhibit Kv channels by binding to VSD. However, the structural basis for the inhibition remains elusive. Here, fluorescence and NMR analyses of the interaction between VSD derived from KvAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 46 publications
7
13
0
Order By: Relevance
“…This value would represent the equilibrium dissociation constant between the lipid partitioned ligand and the lipid embedded receptor. Remarkably, however, the value is in good agreement with equilibrium dissociation constants measured between micelle embedded receptors and free ligands [48,55,64].…”
Section: 'Membrane Catalysis' As a Kinetic Model For Contribution Of supporting
confidence: 83%
See 1 more Smart Citation
“…This value would represent the equilibrium dissociation constant between the lipid partitioned ligand and the lipid embedded receptor. Remarkably, however, the value is in good agreement with equilibrium dissociation constants measured between micelle embedded receptors and free ligands [48,55,64].…”
Section: 'Membrane Catalysis' As a Kinetic Model For Contribution Of supporting
confidence: 83%
“…Similarly, GMTs such as hanatoxin [59,60], ProTx-II [61], HHN2B-G7W [53] and SGTx [62] have been shown to bind to lipid bilayers. These and several other studies have also consistently shown that these cationic GMTs have an increased affinity for anionic lipids [48,55,63,64]. The distribution of the basic residues on the GMTs forms a basic patch surrounded by hydrophobic residues creating an amphipathic structure which has been suggested to mediates membrane association by several biophysical studies as well as molecular dynamics simulations [48,[64][65][66].…”
Section: Binding Kinetics Of Spider Toxin Gating Modifierssupporting
confidence: 55%
“…In order to investigate the voltage-dependent conformational change of VSD, we used the V119C mutant, in which the Cys119 residue was chemically modified by a fluorescent dye, monobromobimane (mBBr), as previously reported20 (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…The cells were grown at 37 °C to an A 600 of 0.4–0.6, and protein expression was then induced with 1.0 mM isopropyl-β-D-thiogalactopyranoside for 3–6 hours at 37 °C. Purification of the MBP-VSD was described elsewhere20. For the reconstitution of the purified proteins, the buffer was exchanged with “liposome buffer”, containing 20 mM Hepes-NaOH, pH 8.0, 0.10 mM KCl, 149.9 mM NaCl, and 10%(v/v) glycerol, in the presence of 2 mM DM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation